2011
DOI: 10.1111/j.1532-5415.2010.03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Month-Long Napping Regimen in Older Individuals

Abstract: OBJECTIVES 1) To examine the effects of a month-long nap regimen using one of two durations (45 min, or 2 hr) on nighttime sleep and waking function in a group of healthy older subjects. 2) To assess the degree to which healthy older individuals are willing/able to adhere to such napping regimens. DESIGN Three laboratory sessions, with 2-week at-home recording interspersed, using a between-subjects approach. SETTING The study was conducted in the Laboratory of Human Chronobiology at Weill Cornell Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Additionally, in our study, napping did not maintain the cognitive function levels in the Itype and E-type elderly adults. This result is consistent with the results from previous experimental studies (Campbell, Stanchina, Schlang, & Murphy, 2011;Monk et al, 2001), suggesting that elderly adults with different chronotypes may exhibit differences in cognitive function level. In the future, studies with a longitudinal design should be conducted to validate this result.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in our study, napping did not maintain the cognitive function levels in the Itype and E-type elderly adults. This result is consistent with the results from previous experimental studies (Campbell, Stanchina, Schlang, & Murphy, 2011;Monk et al, 2001), suggesting that elderly adults with different chronotypes may exhibit differences in cognitive function level. In the future, studies with a longitudinal design should be conducted to validate this result.…”
Section: Discussionsupporting
confidence: 93%
“…Yet, contrary to this thinking, others demonstrated in healthy adults that afternoon naps produced little effect on the duration or quality of subsequent nighttime sleep; moreover, 24-hour sleep time was increased and those who napped had better cognitive and psychomotor performance after the nap and over the day (36). Daytime napping can also improve emotional state (37).…”
Section: Discussionmentioning
confidence: 99%
“…Three such studies in samples of midlife women and older adults reported no changes in PSG-assessed nocturnal sleep following daytime napping. 118-120 Similarly, Campbell and colleagues reported no significant changes in PSG-assessed sleep of older adults following a daytime nap, with the exception of a small but significant increase in SOL (from 16 to 22 minutes). 121 In contrast, others have found that implementing a daytime napping schedule does negatively impact PSG-assessed sleep.…”
Section: Empirical Support For Individual Sleep Hygiene Recommendationsmentioning
confidence: 98%